Marine Mammals (Springer Nature, 2023)
This highly-readable Open Access textbook provides basic background information about marine mammals and anthropogenic impacts on them. The book includes inspiring exercises for education school programs in natural sciences. The book also provides advice on career paths using case studies of marine scientists and veterinarians describing their journeys from student to profession. By sharing real-life career paths, readers find answers to questions such as “What needs to be considered when choosing a career in science?” and “What kind of tasks do scientists undertake on a daily basis?” Marine mammals are amongst some of the most celebrated creatures on Earth, with their high intelligence, social and communicating skills, and capacity for deep diving. Alongside general information about marine mammals, the book aims at generating awareness of the impact of litter and noise pollution on the marine environment using marine mammals as an example. Huge numbers of marine animals, including marine mammals, die every year from entanglement in fishing gear, by ingestion of litter or because of chemical pollution. In the last decade many technological and scientific tools have been developed to aid research, for instance miniaturised sound recorders which can be attached to cetaceans and seals and record noise levels around them, their vocal production as well as their diving behaviour. This Open Access textbook can be used by undergraduate students interested in the fundamentals of marine mammal biology and medicine, and in pursuing the profession of a marine scientist.